Politicization of the press in selected opinion-forming weeklies. Preliminary research report - Brzoza, Katarzyna; Głuszek-Szafraniec, Dagmara; Szostok, Patrycja (Political Preferences, 2017)
The aim of this article is to present the results of a research on media and policy relations in Polish media system. The authors use acontent analysis of the press to show the bias of the Polish weekly and an attitude of editors to a specific subject in political context. The analysis of presented results shows a specific model of journalism and the model of media-politics relations in Poland. Key words: political paralelism, media in Poland, opinion press